Human Amniotic Membrane Plug for Macular Holes Coexisting with Rhegmatogenous Retinal Detachment - Abouhussein MA (Dove Medical Press, 2020)
Mahmoud Alaa Abouhussein, Samir Mohamed Elbaha, Mohsen Aboushousha Ophthalmology, Alexandria University, Alexandria, EgyptCorrespondence: Mahmoud Alaa AbouhusseinOphthalmology, Alexandria University, 8 Hassan Allam Street, Kasr Elmoltazem Building, Smouha, Alexandria 1103, EgyptTel +20 1001026075Email nad03alaa@yahoo.comPurpose: To evaluate the efficacy of human amniotic membrane in promoting closure of macular holes coexisting with rhegmatogenous retinal detachment.Methods: This is a retrospective case series of 14 eyes (14 patients) with macula off retinal detachment. These patients had a macular hole coexistent with peripheral retinal breaks. A human amniotic membrane plug was used to close the macular hole during vitrectomy without ILM peeling.Results: The mean preoperative BCVA (logMAR value) was 1.87 ± 0.31. At the 6-month follow-up visit, the mean LogMAR best-corrected visual acuity was 0.67 ± 0.17. At the 6-month follow-up, all patients showed complete retinal reattachment with macular hole closure.Conclusion: The use of human amniotic membrane is a valid option in surgery for macular holes coexisting with rhegmatogenous retinal detachment.Keywords: human amniotic membrane, macular hole, rhegmatogenous retinal detachment